Development of Virtual Mentor-Based Chembo Learning Media to Improve The Learning Outcomes of Science Education Students - Mellyta Uliyandari; Nirwana Nirwana; Sutarno Sutarno (Vidya Karya, 2023)
This study aims to develop Chembo (Chemical Bond) learning media based on Virtual Mentors to improve student learning outcomes in Science Education on Chemical Bonds. The research method used is research and development with 4D (four-D) design, namely definition, design, development, and deployment. The instruments used in this research were questionnaires and pretest and posttest questions. The results of the study show that the results of material validation by material experts are at number 72 which is in the "Very Eligible" category, while the validation results by media experts are 55, which is in the "Very Eligible" category. The results of students' assessment of the feasibility of learning media were in the "Very feasible" category with a conversion score of 33.82. Data on the results of student responses to chembo learning media get a value of 246.5 which, if converted, will get a value of 4.24 in the "strongly agree" category. Student learning outcomes after using Chembo learning media also experienced an increase seen from the comparison between students' pretest and posttest scores. The average score of students' pretest before using Chembo media was 48.97, while the average posttest score of students after using Chembo media was 80.86. The students' pretest and posttest gain test results scored 0.62 in the "Medium" category. Based on the study's results, it can be concluded that chembo learning media is very feasible to use in supporting the learning process and can improve student learning outcomes, especially in chemical bonding material.